Bonded Excimer Formation in π‑Stacked 9‑Methyladenine Dimers - Spata, Vincent A; Matsika, Spiridoula (The journal of physical chemistry. A, Molecules, spectroscopy, kinetics, environment, & general theory, 2013)
The interaction of DNA with UV radiation is an area of intense interest not only because of its biological implications but also because of the complicated excited state dynamics. To channel the excess energy associated with the absorption of UV radiation, the nucleobases undergo ultrafast nonradiative decay facilitated by conical intersections. In this work we extend the role of conical intersections in π-stacked dimers of nucleobases. We present a novel conical intersection between the excited state and the ground state for a π-stacked 9-methyladenine homodimer system, where a bond is partially formed between the two bases, and the wave function shows charge-transfer character between the monomers. These characteristics lead us to assign this state to a bonded excimer, a model that has been proposed in the past to explain the observed electron transfer in systems where this process is not thermodynamically favored. Gas-phase excited state calculations are carried out using perturbation theory corrected configuration interaction singles methods and complete active space self-consistent field, and physical observables are calculated and analyzed to understand the behavior of the system. A polarizable continuum solvent model is used to test the changes of the energies of the excited states along the pathway subject to solvation and reveals small changes in aqueous solution. Molecular dynamics simulations have also been performed on a poly(dA)20·(dT)20 B-DNA strand to find how the backbone affects the proximity of the bases which can facilitate access to the conical intersection.